Salinity tolerance of larvae Aedes aegypti inland and coastal habitats in Pasangkayu, West Sulawesi, Indonesia - ARINI RATNASARI; ARIF RAHMAN JABAL; SYAHRIBULAN SYAHRIBULAN; Irfan Idris; NUR RAHMA; SRI NUR RAHMI NUR RUSTAM; MILA KARMILA; HAJAR HASAN; ISRA WAHID (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ratnasari A, Jabal AR, Syahribulan, Idris I, Rahma N, Rustam SNRN, Karmila M, Hasan H, Wahid I. 2021. Salinity tolerance of larvae Aedes aegypti inland and coastal habitats in Pasangkayu, West Sulawesi, Indonesia. Biodiversitas 22: 1203-1210. Aedes aegypti L. is the primary arboviral vector generally found in freshwater, but it is also observed in brackish water. The study analyzes habitat characteristics, larvae adaptation, and oviposition preference in salinity levels over the coastal and inland ecosystem in Pasangkayu District of West Sulawesi. The larvae were reared until adults and have larval of first progeny were examined the salinity tolerance in five salinity levels. Ovitrap-based experiments were carried out in the laboratory using adult Ae. aegypti colonies from inland and coastal areas. Eggs on filter paper (ovitrap) were identified and counted. Data were analyzed using LC50 (larvae with salinity tolerance) and Pearson correlation (correlation between the larvae phase two ecosystem factors). Total larvae observed in coastal areas and inland are 1437 and 1288, respectively. The salinity tolerance test showed that Instar IV is highly adapted to the saline environment. The larvae from the coastal (inland) area can tolerate salinity up to 13 (10) ppt. Mosquitoes can lay many eggs in 3 ppt salinity: 27.1% and 20.8% for coastal and inland colonies, respectively. Pearson correlation analysis showed a significant correlation between the larval instar stage of Ae. aegypti from coastal and inland ecosystems with the ability to survive at the salinity level (p < 0.01). This study is expected to be a source of information on the adaptation of Ae. aegypti mosquito to salinity in coastal and inland ecosystems. The findings can be considered in vector control efforts on brackish water habitats.